DSIL4IMR: A dual step-based initial localization method for industrial mobile robot - Li Wenguang; Ou Jishun; Ren Jiying; Huang Panling; Fang Haibo; Han Lu; Zhou Jiehan; Zhou Jun (MATEC Web of Conferences, 2024)
This paper introduces a dual-step based initial localization method for industrial mobile robots (DSIL4IMR) that operates without user intervention at start-up. Utilizing a differential chassis equipped with a radar sensor, the method combines feature extraction and spatial information matching steps to locate the robot’s initial position. A unique metric, degree of stability, is developed to identify a feature map whether it is a dynamic or erroneous feature. DSIL4IMR does not require artificial landmarks and outperforms existing WiFi fingerprinting and map filter methods in both accuracy and efficiency. DSIL4IMR triples the localization efficiency compared to traditional approaches while achieving centimetre-level precision.